Spionase Pejabat Diplomatik Rusia Terhadap Negara Denmark Dalam Hukum Diplomatik - Sya’ban, Balgis; Tahamata, Lucia Charlota Octovina; Hanafi, Irma Halimah (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Espionage is intelligence activity in a country or company seeking confidential information. Espionage activities focus on gathering non-public information through covert means. Espionage by Russian diplomatic officials against Denmark led to the expulsion of Russian diplomatic officials due to unacceptable espionage in Denmark. The purpose of this study is to examine and discuss whether Russian espionage can be categorized as espionage and how responsibility for espionage is carried out by Denmark.Purposes of the Research: To study and discuss whether Russian spying experiments can be categorized as espionage and how is the responsibility for espionage carried out by Russia against Denmark.Methods of the Research: The research method used is normative juridical, namely research on rules, norms, and legal principles based on statutory regulations. The problem approach used is the normative legal approach, namely the conceptual approach, the case approach and the statutory approach. The sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. Legal material collection techniques through library research. Then analyzed qualitatively.Results of the Research: The results of the study conclude that spying by Russian diplomatic officials against Denmark can be categorized as espionage because it is contained in the 1961 Vienna convention. eye is considered espionage. The form of accountability for the Danish state due to actions committed by the Russian state is by expelling or persona nongrata against diplomatic officials who carry out espionage.